Imaging liver nodules in tyrosinemia type-1: A retrospective review of 16 cases in a tertiary pediatric hospital. Issue 116 (July 2019) - Ozcan, H. Nursun; Karcaaltincaba, Musturay; Pektas, Emine; Sivri, H. Serap; Oguz, Berna; Dursun, Ali; Tokatli, Aysegul; Coskun, Turgay; Haliloglu, Mithat
Highlights: Fatty liver nodules might be observed in HT1 patients and they can display morphological changes during the follow up. Every liver nodule might not always/necessarily be HCC, close follow up -preferably with MR imaging- should be performed in addition to clinical and laboratory findings where HCC is suspected. Alpha-fetoprotein (AFP) values and liver imaging should be carried out periodically for early detection of HCC in HT1 patients. Abstract: Objective: To describe the liver imaging findings of Hereditary tyrosinemia type-1 (HT1) patients. Materials and methods: We report 16 patients (8 Female and 8 Male) with HT-1. Their demographic features, imaging findings and alpha feto protein (AFP) levels were recorded. Imaging features on CT and MR were evaluated for the following characteristics: contour of the liver and liver nodules. Liver nodules were categorized as; regenerative, dysplastic, fatty and malignant nodules (HCC). Results: Thirteen (81%) patients had multiple liver nodules (>20) on imaging studies. Five patients (31%) had regenerative nodules, six (38%) had dysplastic nodules and ten (63%) had fatty nodules. Dysplastic nodules were encountered in two patients with HCC and in four patients without a tumor. Four patients (25%) had HCC nodule on imaging studies. Those four patients had biopsy and all of them had HCC nodule on histopathology. In the follow-up period, in one patient fatty nodules had increased in size, in one patient regenerative nodules had disappeared and in one patient dysplastic nodules had disappeared. Conclusions: Multiple fatty nodules can be seen in HT1 patients and in some patients, the regenerative and dysplastic nodules can disappear during the follow-up period.